Menghadapi Tantangan Pendidikan Islam di Indonesia: Antara Modernisasi dan Nilai Tradisional - Winarno, Dwi; Sukari, Sukari (Lembaga Yasin AlSys, 2024)
Islamic education in Indonesia is currently facing major challenges in facing modernization, which demands adjustments without sacrificing traditional values. This article is a literature study that analyzes how Islamic education can adapt to the demands of modernization while still preserving traditional values. This study examines various literatures that discuss curriculum integration between religious and general sciences, the importance of character education, and increasing teacher capacity in the context of modernization. The results of the analysis show that curriculum integration can create graduates who are knowledgeable and have a strong understanding of religion. In addition, strengthening character education based on Islamic values ​​is important to shape students' identity and morals. This study also emphasizes the need for collaboration between educational institutions, government, and society to support relevant Islamic education. Thus, this article provides strategic guidance to maintain a balance between modernization and preservation of traditional values ​​in Islamic education in Indonesia.